Option C
The zeros of the polynomial function f(x) = x^3 - 5x^2 - 6x is x = 0 and x = -1 and x = 6
<h3><u>Solution:</u></h3>
Given that polynomial function is f(x) = x^3 - 5x^2 - 6x
We have to find the zeros of polynomial
To find zeros, equate the given polynomial function to 0. i.e f(x) = 0
![x^3 - 5x^2 - 6x = 0](https://tex.z-dn.net/?f=x%5E3%20-%205x%5E2%20-%206x%20%3D%200)
Taking "x" as common term,
![x(x^2 - 5x - 6) = 0](https://tex.z-dn.net/?f=x%28x%5E2%20-%205x%20-%206%29%20%3D%200)
Equating each term to zero, we get
![x=0 \text { and } x^{2}-5 x-6=0](https://tex.z-dn.net/?f=x%3D0%20%5Ctext%20%7B%20and%20%7D%20x%5E%7B2%7D-5%20x-6%3D0)
Thus one of the zeros of function is x = 0
Now let us solve ![x^{2}-5 x-6=0](https://tex.z-dn.net/?f=x%5E%7B2%7D-5%20x-6%3D0)
We can rewrite -5x as -6x + x
![x^2 + x - 6x - 6 = 0](https://tex.z-dn.net/?f=x%5E2%20%2B%20x%20-%206x%20-%206%20%3D%200)
Taking "x" as common from first two terms and -6 as common from next two terms
![x(x + 1) -6(x + 1) = 0](https://tex.z-dn.net/?f=x%28x%20%2B%201%29%20-6%28x%20%2B%201%29%20%3D%200)
Taking (x + 1) as common term,
(x + 1)(x - 6) = 0
x + 1 = 0 and x - 6 = 0
x = -1 and x = 6
Thus the zeros of given function is x = 0 and x = -1 and x = 6